Peningkatan Literasi Keuangan Siswa SMA Melalui Pelatihan Pengelolaan Keuangan Pribadi - Yuyun Kurniawati; Nurul Ali Hidayat; Diki Kurniawan (Journal of Empowerment Community, 2026)
The purpose of this Community Service (PKM) is to improve financial literacy, awareness, and the ability of high school students (SMA) to manage their personal finances from an early age. Good personal finance management is an essential skill that will help students achieve their financial goals and prevent financial problems in the future. The training provided included how to budget their daily personal money. The methods used are a combination of lectures, discussions, case studies, and practical training. The results of this service show a significant improvement in all aspects of participants' financial literacy after the training. High school students have a fairly good level of awareness about the importance of personal financial management, but still lack practical skills in creating income and expense budgets and savings awareness. Therefore, it is recommended that the school include material on financial literacy into the literacy habits the school has already been practicing. Additionally, students also need to be proactive in seeking information and learning from various sources about personal financial management. With adequate knowledge and skills, students are better prepared to face future financial problems and achieve financial freedom.